Photonic powering of sensors with bidirectional communication along a single fiber - Shikoski, Jovan; Arnaudov, Rumen; Eftimov, Tinko (Photonics Letters of Poland, 2020)
In this paper we propose and study simultaneous transmission of photonic power and bidirectional communication to and from sensors via 840/1310 nm WDMs. The photovoltaic converter is used both for power conversion and data transfer from the high power laser at 808nm up to 1Mb/s while the 1310nm link can be up to 155 Mb/s. Full Text: PDF References: J.C.V.da Silva, E.L.A.S.de Souza, V.Garcia, J.B.Rosolem, C.Floridia, M.A.B.Sanches, "Design of a Multimode Fiber Optic Cable to Transmit Optical Energy for Long Reach in PoF Systems", Proceedings of the 63rd IWCS Conference, International Wire & Cable Symposium, Shrewsbury, PA, USA, 2014, pp.832-839. [CrossRef] J.B. Rosolem, E.K.Tomiyama, D.C.Dini, F.R.Bassan, R.S.Penze, A.A.Leonardi, C. Floridia, J.P.Fracarolli, R.M.Teixeira, "A fiber optic powered sensor designed for partial discharges monitoring on high voltage bushings". Proc. of SBMO/IEEE MTT‐S International Microwave and Optoelectronics Conference (IMOC); 3-6 Nov. 2015; Porto de Galinhas, Brazil, pp. 1-5. [CrossRef] T.C. Banwell, R.C.Estes, L.A.Reith, P.W.Shumate, E.M.Vogel, "Powering the fiber loop optically - a cost analysis", IEEE J. of Lightwave Techn., Vol. 11, No. 3, pp. 481-494, 1993. [CrossRef] M. Dumke, G. Heiserich, S. Franke, L. Schulz, and L. Overmeyer, "Power Transmission by Optical Fibers for Component Inherent Communication", Systemics, Cybernetics And Informatics, Vol.8, No.1, pp. 55-60, (2010) [DirectLink] C. Gao, J. Wang, L. Yin, J. Yang, J. Jiang, H. Wan, Optically Powered Active Sensing System for Internet Of Things, Proc. SPIE 9270, Optoelectronic Devices and Integration V, 927016 (24 October 2014) [CrossRef] J. Yan, J. Wang, Y. Lu, J. Jiang, H. Wan, Novel Wireless Sensor System Based on Power-over-Fiber Technique, 14th Int. Conf. on Optical Comm. and Networks (ICOCN) 3-5 July 2015, Nanjing, China, 15382393 [CrossRef] Böttger, G.; Dreschmann, M.; Klamouris, C.; Hü bner, M.; Röger, M.; Bett, A. W.; Kueng, T.; Becker, J.; Freu de, W.; Leuthold, J.: An Otically Powered Video Camera Link. IEEE Photonics Technology Letters, Vol. 20, No. 1, pages 39-41, 2008. [CrossRef] M. Matsuura and J. Sato, Bidirectional Radio-Over-Fiber Systems Using Double-Clad Fibers for Optically Powered Remote Antenna Units, IEEE Photonics J., Vol. 7, No. 1, 2015, 7900609 [CrossRef] J. Wang, Q. Li, J. Yan, Y. Ding, Y. Lu, Y. Zhang, H. Wan, Power-Over-Fiber Technique based Sensing System for Internet оf Things, 15th International Conference on Optical Communications and Networks (ICOCN), Hangzhou, China, Sep. 24-27, 2016. [CrossRef] S. Kartalopoulos, Optical Bit Error Rate: An Estimation Methodology (2004) Willey- IEEE Press. [CrossRef] J. Shikoski, R. Arnaudov, and T. Eftimov, A study of the frequency characteristics of a photovoltaic convertor РРС-4Е, Photonics Letters of Poland, Vol. 10(3), (2018), pp. 70-72 [CrossRef] J. B. Rosolem, Optical Fiber and Wireless Communications, Ed. by R. Róka, Ch. 13, Power‐Over‐Fiber Applications for Telecommunications and for Electric Utilities, Intech Open Ltd, London, 2017, pp.255-278. [CrossRef]